Republicanismo e participação política em Rousseau - Sá, Antônio Marcos Alves (2012)
The relationship between republicanism, understood as a current of thought, and political participation in the political thought of Jean-Jacques Rousseau, is the subject of this dissertation, which sought to highlight the features that identify it as a tax author of classic republican tradition, which is represented by thinkers such as Aristotie, Cicero and Polybius. Therefore, it was necessary to examine the context in which the republican ideas that were formulated swiss thinker and the role of such participation taking as fundamental book The Social Contract or Principies of Political Right. The Rousseau republicanism assumes, besides the establishment of conventions, the juxtaposition of other key elements such as virtue, humanism and civic education. This triad sustained their theses about the republic of "popular sovereignty". freedom and the general will, the latter expressed in the form of laws that will, according to Rousseau, to guide the actions of citizens and to distinguish the boundary baus public and private. But how could the connection between the will and the particular "public thing", without the first the second master? What are the limits to this "sovereignty"? Anyway, as a political theory, sustained virtuosity in civic, could still influence contemporary political reflection with regard to political participation, understanding the term "people" while citizens exercising their voting power? The clues to answer the questions posed are perceived in that the author defends his thesis on the necessity of maintaining the sovereign and the public sphere as an exercise of real freedom, which resulted in the institution of the figure of the legislator, who is responsible by establishing and preserving the foundations ofthe republic and promote the public interest by "common good" and respect for the sovereign acts, since their actions are only able to reconcile civil liberty and public dependency. These concepts have maintained the relevance of the writings of Rousseau for discussions about republicanism, the "public thing" and theories of modern democracy, where the concept of freedom formulated by the "Citizen of Geneva" was taken as an ideal maintenance of reciprocal relationship between community members and political affinity between it and the State. Thus, to be free is not only restricted to the idea of "nondomination", the freedom is directly related to the actions of individuals as members of the politicians.